Broadband photothermal enhancement in direct absorption solar collectors using blended plasmonic Ag nanofluids - Hashim, Ghasaq Adheed; Tan Lit, Ken; Eleen Dayana, Isa; Mohd Nashrul, Mohd Zubir; Alawi, Omer A.; Mallah, Abdul Rahman; Lee, Kee Quen; Wong, Keng Yinn; Shahirah, Abu Bakar; Ngien, Su Kong; Chuan, Zun Liang; Siang, Gan Yee (Elsevier Ltd, 2026)
Achieving broadband plasmonic absorption across the entire solar spectrum remains a critical challenge for direct absorption solar collectors (DASCs), as single-morphology nanoparticles exhibit narrow spectral response limited to specific wavelength bands. This study introduces a quaternary morphological blending strategy that synergistically combines four distinct Ag nanoparticle geometries, nanocubes, nanodisks, nanoprisms, and nanorods to achieve continuous spectral coverage from 300 to 1500 nm. Finite element method (FEM) simulations optimized dimensional parameters for each morphology, while three-dimensional CFD modeling with the discrete ordinate radiation model (DORM) evaluated DASC thermal performance. The optimized blend (31% nanocubes, 23% nanodisks, 25% nanoprisms, 21% nanorods) achieved 99.4% spectral photothermal conversion efficiency at an ultra-low concentration of 0.0002 vol%, representing a 301.2% enhancement over pure water, while three-dimensional CFD modeling computationally predicted a DASC thermal efficiency of 83.3% at Re = 77, accounting for thermal losses and scattering effects. Sensitivity analysis confirmed system robustness, with all perturbed configurations maintaining efficiencies exceeding 97%. This quaternary approach establishes a new paradigm for nanofluid engineering, demonstrating that morphological diversity rather than increased particle loading governs optimal solar thermal conversion.